Assessment of mobility in working age stroke patients during the Covid-19 pandemic - Bosacka, Małgorzata Grażyna; Bączyk, Grażyna (Nursing in the 21st Century, 2023)
ASSESSMENT OF MOBILITY IN WORKING AGE STROKE PATIENTS DURING THE COVID-19 PANDEMICAim. Early neurological rehabilitation is essential to regain functional efficiency and achieve an optimal level of independence, especially during the COVID-19 pandemic. The objective of the work was to assess the functional performance of patients of working age after hemorrhagic or ischemic brain stroke admitted to the neurological rehabilitation unit and to assess additional factors affecting the effectiveness of neurological rehabilitation.Material and methods. The study group included 89 patients admitted to the neurological rehabilitation unit. The eligibility criterion for the treatment group was the age of 25-55 years (professionally active people) and the suffered hemorrhagic or ischemic brain stroke. The functional performance assessment was performed using the Barthel Index and the NHPT (Nine Hole Peg Test) test. Sociodemographic data were obtained from the analysis of medical records. The survey was conducted on the first and last day of stay.Results. There was a significant impact of age on the type of stroke, with people with an ischemic stroke being indeed statistically older than those with hemorrhagic stroke (50± 5 years), compared to those with hemorrhagic stroke (46± 8 years). It has been established that the time spent in a unit is dependent on the age of the patient, the older the patient the longer the hospitalization lasts. The tests assessing the functionality of the hands have showed statistically significant improvements in the study group. It has been demonstrated that the improvement of functional performance depended on gender. People with diabetes performed statistically worse (Me=28 vs. Me=21).Conclusions. 1. Older people after stroke need more time to rehabilitate. 2. There is a need for more rehabilitation in people with diabetes. 3. Longer rehabilitation for men is advisable regardless of the type of stroke.